The impact of strategic leadership on achieving organizational excellence - A Field Study on the Ministry of Commerce and Investment in the Governorate of Jeddah - - Samaraddin, Rasha Rashad; Alqurashi, Suzan Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to identify and recognize the effect of strategic leadership in its dimensions namely (strategic trend, human capital, organization culture, and organizational control) over achievement of organizational excellence in the Ministry of Commerce and Investment, Jeddah. It further aims to verify whether there are statistically indicated differences among the responses provided by members of the sample group over the strategic leadership and organizational excellence in the Ministry of Commerce and Investment in Jeddah; and whether such could be attributed to personal and occupational variables such as the following: (gender, age, education, years of experience and job title). To this aim, the researcher has employed the descriptive analytical approach. In addition, the study had a questionnaire together with interviews as tools to collect data. Community of the study was composed of (200) employees of both genders. A simple sample group composed of (132) members was selected. Collected data were statistically processed through the SPSS. The study concluded a number of important findings. Following are among of these findings: Strategic leadership in the Ministry of Commerce and Investment, Jeddah, has achieved high levels, The arithmetic mean stood at (3.81), the Ministry has managed to achieve high levels in terms of organizational excellence where the arithmetic mean has reached (3.75). The study has further revealed statistically indicated reference at the indication level of (ɑ ≤ 0.05) for the strategic leadership with its dimensions incorporated in (Strategic Trend, Human Capital, Organizational Culture, and Organizational Control). All are combined to achieve organizational excellence in the Ministry. On another hand, the study revealed absence of any statistically indicated differences at the indication level of (ɑ ≤ 0.05) between the responses of participants over strategic leadership and organizational excellence in the Ministry that would be attributed to the following personal and occupational variables: (gender, age, education, years of experience, and job title). Eventually, the study concluded a number of significant recommendations as follows: Strategic Leadership shall be urged to analyze the internal and external milieu in order to identify the points of strength and weakness, opportunities and threats (SWOT Analysis) likely to encounter the Ministry. The study further recommended a special system be put in force to recruit human cadres into the Ministry so as to appoint high caliber employees.
Keywords: strategic leadership; organizational excellence; Ministry of Commerce and Investment